Studi Komparasi Asal-Usul Manusia Berdasarkan Teori Evolusi Darwin Dan Berdasarkan Alkitab - Fransius Kusmanto; Jernih Halawa (Sekolah Tinggi Teologi Pontianak, 2024)
Human origins are a topic that needs to be explored. Throughout history, there have been many theories about human origins. Some of these theories are based on Darwin's theory and the Bible. Both theories view human origins from their own perspectives. Darwin's theory of evolution states that humans are the result of a gradual biological process involving natural selection, genetic variation, and adaptation to the environment, with ancestors originating from primates, supported by fossil evidence and the